Faktor-Faktor Bioekologi pada Komitmen Pernikahan Tenaga Kerja Wanita Asal Indramayu - Melok Roro Kinanthi; Adriana Ginanjar; Winarini Wilman (Jurnal Psikologi Islam dan Budaya, 2018)
The aim of this study was to explore ecological factors that contribute to marital commitment of the female migrant workers in Indramayu. This study applied qualitative approach with case study design. Data were obtained by semi structure interview, focus group discussion, observation, and document analysis. This study was conducted in Village X because this village is one of the biggest contributors of female migrant workers. Participants of this study were female migrant workers, government’s institution staff, villagers, who were selected by purposive sampling method. The finding of this study shows that the dynamic of marital relation among female migrant workers were the result of dynamic interaction bertween macrosystem, exosystem, mesosystem, and microsystem context. Thus, the intervention should be done not only in dyadic context, but also should be directed in macro context.